Distortions to agricultural incentives in Cameroon : Main report - Bamou, Ernest; Masters, William A. (Washington, DC: World Bank, 2022)
Cameroon is among the more prosperous countries in Africa, thanks to relatively abundant agricultural land and offshore petroleum. These spurred an economic boom from unification of the country in 1972 until 1986, which was followed by a decade of decline from 1986 to 1995 and a limited recovery since then. Prior to the economic crisis of the late 1980s, Cameroon's development strategy efforts were managed through a series of five-year development plans. In these, agriculture was described as the priority sector and the government intervened massively in rural development, both directly through the establishment of state-owned agro-industries, rural corporations and settlements, and also indirectly through various support programs. Later reforms and the devaluation of 1994 improved performance through allowing more market incentives to play a role. In this chapter the authors use the methodology of Anderson et al. (2008) to quantify the evolution of those distortions to farmer incentives, measuring the incidence of government policy on producers and consumers each year in Cameroon from 1961 to 2004. For each of the major activities we compute Nominal Rates of Assistance (NRAs), which are then aggregated into a variety of other indexes. The chapter is organized as follows. The next section provides a brief overview of agriculture's role in the economy. A summary of the main agricultural policy incentives, interventions and reforms is then provided, before describing the country's growth performance over time. The main section computes and analyzes government distortions to agricultural incentives, and the concluding section speculates on prospects for future policy reform.